Media Sosial sebagai Lingkungan Pendidikan Islam : Analisis Pemikiran Hasan Langgulung - Siti Mabruroh; Muhammad Arif Syihabuddin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to understand the essence and role of the Islamic educational environment according to Hasan Langgulung, and examine its relationship with social media as part of the educational environment in the digital age. This study applies a qualitative approach with a literature study type, sourced from books and scientific articles related to Hasan Langgulung's thoughts, the educational environment, and social media. Data collection was conducted through documentation studies, and data analysis used content analysis methods. The research findings indicate that the environment plays an important role in internalizing Islamic values ​​and shaping students' character, while social media has the potential to function as a non-formal educational environment that supports the learning process, the dissemination of Islamic values, and the strengthening of Muslim identity in the digital world. However, social media also presents challenges in the form of the dissemination of inaccurate religious information and the potential for moral degradation. Therefore, the integration of the concept of the Islamic educational environment with social media requires targeted management and the active role of educators and families so that social media remains within the corridor of Islamic educational values ​​and supports the achievement of Islamic educational goals.